INOVASI PEMBELAJARAN MUFRADAT MELALUI DIGITAL STORYTELLING: MENGOPTIMALKAN PENGUASAAN KOSAKATA BAHASA ARAB - Azhari, Jalaludin Faruk (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2025)
This study investigates the use of digital storytelling for learning Arabic vocabulary at the Madrasah Tsanawiyah (MTs) level. Conventional vocabulary learning frequently encounters challenges in the form of boring procedures, a lack of contextualization, and poor student motivation. In the digital era, incorporating technology into Arabic language study is essential for improving learning efficacy. Digital storytelling is an innovative approach that mixes traditional narratives with multimedia elements such as photos, audio, and video. This descriptive qualitative research was carried out at MTs Al-Falah, with data collected through interviews, observations, and documentation. The study's findings show that the use of digital storytelling in vocabulary learning involves two stages: preparation (needs analysis, theme selection, script preparation, media selection, and audio-visual component preparation) and implementation (introduction, concept formation, digital storytelling production, evaluation, and reflection). The benefits include improved vocabulary mastering, learning motivation, the development of digital skills and creativity, and collaborative learning. Challenges include limited infrastructure, teacher technology competency, scheduling constraints, a shift in concentration to technological factors, and limited Arabic resources. The remedies proposed include the use of alternative technologies, teacher training, collaborative teaching, the use of templates, and a focus on learning objectives. The study's findings are likely to help build new and successful Arabic language learning methodologies for the MTs level.